Untersuchung der Werkstoff-, Prozess- und Bauteileigenschaften beim Fused Deposition Modeling Verfahren - Kloke, Agnes
In dieser Arbeit wurde ein Prozessverständnis für das FDM-Verfahren hinsichtlich der Verarbeitung des Materials Ultem*9085 aufgebaut. Es wurde der Einfluss des Materials, des Prozesses und der Maschine auf die resultierende Bauteilqualität untersucht. Die Materialqualität unterschiedlicher Chargen zeigt, dass Feuchtigkeit im Material die Strangablage beeinflusst. Die Analyse der Prozessparameter, die anhand der Kurzzeitfestigkeiten analysiert wurden, zeigt einen starken Einfluss der Aufbauorientierung. Mittels einer Parameteroptimierung können ferner gleiche Festigkeitswerte wie aus dem Spritzgießprozess erreicht werden. Bei der Untersuchung der Langzeitfestigkeiten wurde festgestellt, dass sich die Festigkeitswerte bei unterschiedlichen Umgebungsbedingungen nicht ändern. Die Untersuchung einiger Anlagenkomponenten auf die resultierende Oberflächengüte, Geometriegenauigkeit und Festigkeitseigenschaften kann den Einfluss von u. a. der Bauraum- sowie der Düsentemperaturen auf die Bauteilqualität zeigen. Zuletzt wurde die Möglichkeit einer Leichtbauanwendung anhand von Sandwich-Prüfkörpern untersucht. Hierbei beeinflussen sowohl die verfahrensunabhängige Mechanik als auch die verfahrensspezifischen Effekte die Festigkeitswerte.

Einfluss prozess-induzierter Defekte auf die Ermüdungseigenschaften metallischer Werkstoffe verarbeitet mittels Laserstrahlschmelzen - Leuders, Stefan
Den additiven Fertigungsverfahren wird ein hohes Potential zugesprochen, die industrielle Fertigung von Bauteilen und Werkzeugen nachhaltig zu ändern. Dies gilt auch für das hier betrachtete Laserstrahlschmelzen, bei dem metallische Werkstoffe in Pulverform verarbeitet werden. Durch den schichtweisen Aufbau können dabei enorme Vorteile gegenüber konventionellen Fertigungsverfahren erzielt werden, was sich u. a. in einem bis dato unerreichten Maß an Geometriefreiheit widerspiegelt. Allerdings werden die Werkstoffeigenschaften teils erheblich durch kurze und intensive Wechselwirkungen zwischen Laser und Werkstoff bestimmt. Hierdurch können sich werkstoff-spezifische Nachteile gegenüber konventionellen Fertigungsverfahren ergeben, die eine weitreichende Etablierung des Laserstrahlschmelzens erschweren. Vor diesem Hintergrund zielt die vorliegende Dissertation auf eine Analyse und ggf. Optimierung der mikrostrukturellen und mechanischen Eigenschaften laserstrahlgeschmolzener Werkstoffe. Der Schwerpunkt liegt hierbei auf einer Ermüdungsbeanspruchung, da Einflüsse prozess-induzierter Defektstrukturen unter dieser Beanspruchungsform besonders deutlich werden. Durch umfangreiche Untersuchungen können dabei Prozessrouten aufgezeigt werden, die für die betrachteten Werkstoffe TiAl6V4 und 316L den detektierten Schädigungsmechanismen Rechnung tragen und somit zu einer technologischen Konkurrenzfähigkeit des Laserstrahlschmelzens führen.
Keywords: Additive Fertigung; Laserstrahlschmelzen; Materialermüdung

Aniela Knoblich: Antikenkonfigurationen in der deutschsprachigen Lyrik nach 1990, Berlin/Boston 2014 (spectrum Literaturwissenschaft/spectrum Literature 44) - Elit, Stefan (Scientia Poetica)

Automatic Composition of Service-based Image Processing Applications - Jungmann, Alexander; Kleinjohann, Bernd (Proceedings of the 13th IEEE International Conference on Services Computing (SCC))
In the Image Processing domain, automated generation of complex Image Processing functionality is highly desirable; e.g., for rapid prototyping. Service composition techniques, in turn, facilitate automated generation of complex functionality based on building blocks in terms of services. For that reason, we aim for transferring the Service Composition paradigm into the Image Processing domain. In this paper, we present our symbolic composition approach that enables us to automatically generate Image Processing applications. Functionality of Image Processing services is described by means of a variant of first-order logic, which grounds on domain knowledge operationalized in terms of ontologies. A Petri-net formalism serves as basis for modeling data-flow of services and composed services. A planning-based composition algorithm automatically composes complex data-flow for a required functionality. A brief evaluation serves as proof of concept.

Modulbasierte Realisierung eines mittels Backpropagation lernenden Neuronalen Netzes auf einem FPGA - Padalkin, Andreas

Setup Optimization Based on Virtual Tooling for Manufacturing in Order to Provide an Intelligent Work Preparation Process - Weber, Jens; Reisch, Raphael-Elias; Schr{\, Christian; Laroque, Christoph

A Multi-User-Collaboration Platform Concept for Managing Simulation-Based Optimization of Virtual Tooling as Big Data Exchange Service - Weber, Jens

Theoretical Concept of Inverse Kinematic Models to determine valid Work Areas using Target Coordinates from NC-programs - Weber, Jens

Sentiment analysis - Geierhos, Michaela (Encyclopedia {\ "a} the business informatics)

Webmonitoring - Geierhos, Michaela (Encyclopedia {\ "a} the business informatics)

On- and Off-Topic Classification and Semantic Annotation of User-Generated Software Requirements - Dollmann, Markus; Geierhos, Michaela (Proceedings of the 2016 Conference on Empirical Methods in Natural Language Processing)

Crawler (focused / not focused) - Geierhos, Michaela (Encyclopedia {\ "a} the business informatics)

Text Mining - Geierhos, Michaela (Encyclopedia {\ "a} the business informatics)

Towards an Economic Theory of Destabilization War - Gries, Thomas; Haake, Claus-Jochen (Peace Economics, Peace Science and Public Policy)

The enzyme-mediated autodeposition of casein: effect of enzyme immobilization on deposition of protein structures - Ruediger, Arne A.; Bremser, Wolfgang; Strube, Oliver I. (Journal of Coatings Technology and Research)

Nanoscaled Biocoatings via Enzyme Mediated Autodeposition of Casein - Ruediger, Arne A.; Bremser, Wolfgang; Strube, Oliver I. (Macromolecular Materials and Engineering)

Influences on the film thickness in the enzymatic autodeposition process of casein - Ruediger, Arne A.; Terborg, Elke; Bremser, Wolfgang; Strube, Oliver I. (Progress in Organic Coatings)

Enzyme-Mediated In Situ Synthesis and Deposition of Nonaggregated Melanin Protoparticles - Strube, Oliver I.; Büngeler, Anne; Bremser, Wolfgang (Macromolecular Materials and Engineering)

Running Out of Words: How Similar User Stories Can Help to Elaborate Individual Natural Language Requirement Descriptions - Baeumer, Frederik Simon; Geierhos, Michaela (Proceedings of the 22nd Conference on Information and Software Technologies (ICIST 2016))

Time models for the classification and identification of production events - Dangelmaier, Wilhelm (Megatrend digitization - potentials of work and company organization)

How to Complete Customer Requirements Using Concept Expansion for Requirement Refinement - Geierhos, Michaela; Baeumer, Frederik Simon (Proceedings of the 21st International Conference on Applications of Natural Language to Information Systems (NLDB 2016))

Wie verhalten sich Aktionäre bei Unternehmenszusammenschlüssen? Modellierung sprachlicher Muster zur Analyse treibender Faktoren bei der Berichterstattung - Stotz, Sophia Charlotte; Geierhos, Michaela (DHd 2016: Modellierung - Vernetzung - Visualisierung. Die Digital Humanities als fächerübergreifendes Forschungsparadigma. Konferenzabstracts)

Ein Verfahren zur simulationsgestützten Optimierung von Einrichtungsparametern an Werkzeugmaschinen in Cloud-Umgebungen - Laroque, Christoph; Weber, Jens; Reisch, Raphael-Elias; Schröder, Christian (Nissen, Volker;Stelzer, Dirk;Straßburger, Steffen;Fischer, Daniel (Hrsg.): Multikonferenz Wirtschaftsinformatik (MKWI) 2016)

Multi-criteria scheduling and control in dynamic and stochastic environments: A contribution to the creation of robust schedules for freight handling in air freight terminals - Boxnick, Simon

Intelligent work preparation in the cloud - Rehage, Gerald; Isenberg, Florian; Reisch, Raphael-Elias; Weber, Jens; Jurke, Benjamin; Pruschek, Peter (wt workshop technology online)

Sustainability of coalitional equilibria within repeated tax competition - Brangewitz, Sonja; Brockhoff, Sarah (European Journal of Political Economy)

Instituciones Literarias - Eke, Norbert Otto (Insula 829-830. Revista de Letras y Ciencias Humanas)

Fuzzy Matching of Comprehensive Service Specifications - Platenius, Marie Christin

Praxisforschung in Übergangsprojekten. Eine doppelte Herausforderung im Spannungsfeld von Wissenschaft und Praxis sowie differenter Praxislogiken - Bührmann, Thorsten; Büker, Petra (Brücken bauen – Praxisforschung zu Übergängen im Bildungssystem. Tagungsband der 18. Jahrestagung Nordverbund Schulbegleitforschung)

Amsterdamer Publikationen zur Sprache und Literatur (Herausgebertätigkeit von Norbert Otto Eke von Bd. 158, 2005, bis Bd. 174, 2016)
Bd. 158: Rodney Taylor: Studies on Leibnitz in German Thought and Literature 1787-1835. Berlin: Weidler 2005. 260 S. Bd. 159: Jonathan Wooley: The Ethical Project in Rolf Dieter Brinkmann’s Westwärts 1&2. Berlin: Weidler 2005. 186 S. Bd. 160: Sara Smart: The Ideal Image: Studies in Writing fort he German Court 1616-1706. Berlin: Weidler 2005. S. 370 S. Bd. 161: Teresa Ludden: ‚Das Undarstellbare darstellen’: Kulturkritik and the Representation of Difference in the works of Anne Duden. Berlin: Weidler 2006. 267 S. Bd. 162: Frank Krause: Klangbewußter Expressionismus. Moderne Techniken des rituellen Ausdrucks. Berlin: Weidler 2006. 322 S. Bd. 163: Birgit Lang: Eine Fahrt ins Blaue. Deutschsprachiges Theater und Kabarett im australischen Exil und Nach-Exil (1933-1988). Berlin: Weidler 2006. 346 S. Bd. 164: Marielle Sutherland: Images of Absence: Death and the Language of Concealment in the Poetry of Rainer Maria Rilke. Berlin: Weidler 2006. 302 S. Bd. 165: Andreas Kramer: Regionalismus und Moderne. Studien zur deutschen Literatur 1900-1933. Berlin: Weidler 2006. 409 S. Bd. 166: Marc Oliver Huber: Zwischen Schlussstrich und „Schönem Gespräch“. Erinnerung bei Thomas Mann. Berlin: Weidler 2007. 275 S. Bd. 167: Gerd Labroisse: Politisch-Historisches in literarischer Form. Zu Günter Grass’ Roman Ein weites Feld. Berlin: Weidler 2008. 310 S. Bd. 168: Svoboda Dimitrova-Moeck: Women Travel Abroad 1925-1932: Maria Leitner, Erika Mann, Marieluise Fleisser, and Elly Beinhorn. Women’s Travel Writing from the Weimar Republic. Berlin: Weidler 2009. 283 S. Bd. 169: Gregory A. Knott: Arnold Stadler: Heimat and Metaphysics. Berlin: Weidler 2009, 212 S. Bd. 170: Christian Frankenfeld: “Über jede Liebe kommt das Gesetz”. Zum Utopieschwund im Werk Thomas Braschs. Berlin: Weidler 2011. 348 S. Bd. 171: Angela Kölling: Writing on the Loose. Reading Florian Illies’s Generation Golf, Maurice G. Dantec’s Périphériques, Joschka Fischer’s Mein langer Lauf zu mir selbst, and Frédéric Beigbeder’s Windows on the World as examples of creative nonfiction. Berlin: Weidler 2012. 248 S. Bd. 172: Thorbjörn Ferber: Nationaler Antisemitismus im literarischen Realismus. Berlin: Weidler 2014. 467 S. Bd. 173: Ivo Theele: Frauen│gestalten. Inszenierte Weiblichkeit in Rainer Maria Rilkes Frühwerk. Berlin: Weidler 2015. 361 S. Bd. 174: Elias Flügge: Zimmer, Raum, Räumungen. Zur Positionierung weiblicher Figuren im ‚Privatraum‘ bei Autorinnen des 20. und 21. Jahrhunderts. Berlin: Weidler 2016. 295 S.

Fußwallwunder Leicester City - Auch in der Bundesliga möglich? Ein ökonomischer Vergleich des Wettbewerbs in der Bundesliga mit der englischen Premier League - Aykanat, Cengiz

Frag die Anwender: Extraktion und Klassifikation von funktionalen Softwareanforderungen aus User-Generated-Content - Dollmann, Markus

Das Vielfaltstableau: Ein webbasiertes Tool zum Erwerb inklusionsrelevanter Basiskompetenzen in der Lehrerbildung. Workshop im Rahmen der Tagung "LehrerInnenbildung für Inklusion - Hochschuldidaktische Fragen und Konzepte" an der Universität Siegen - Büker, Petra
Oktober 2016

Wir haben mehr so unsere Leistung im Hinterkopf…“ Multiprofessionelle Teamarbeit von Erzieher/-innen, Grundschullehrer/innen und Schulsozialarbeiter/innen als Anlass professionsbezogener Profilschärfungen. Beitrag im Rahmen des Symposiums: Multiprofessionelle Zusammenarbeit von Akteuren aus Kita und Grundschule: Implikationen für Profession und Disziplin an der 25. Jahrestagung der Kommission Grundschulforschung und Pädagogik der Primarstufe an der Universität Bielefeld - Büker, Petra; Bührmann, Thorsten
September 2016

Let us participate! What children tell us about professional support for wellbeing and learning in transition processes from kindergarten to school. Symposiumsbeitrag im Rahmen der 26 th EECERA conference - European Early Childhood Research Association. Universität Dublin, Irland - Büker, Petra
September 2016

Vielfalt aus der Perspektive von Kindern. Fachgespräch am Thementisch. Konferenz der Vielfalt. Universität Paderborn - Büker, Petra
September 2016

Let us participate! What children tell us about professional support for wellbeing and learning in transition processes from kindergarten to school. Symposiumsbeitrag im Rahmen der 26th EECERA conference - European Early Childhood Research Association. Universität Dublin, Irland - Büker, Petra; Bethke, Cathleen
September 2016

Bildungshäuser als interinstitutionelle Bildungsräume für Kinder und pädagogische Fachkräfte – eine systemtheoretische Fundierung. Beitrag im Rahmen des Symposiums: "Bildungshäuser – neue Räume der Bildung für Kinder" an der 25. Jahrestagung der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE) mit dem Themenschwerpunkt "Räume für Bildung. Räume der Bildung". Universität Kassel - Büker, Petra; Bührmann, Thorsten
März 2016

Features of IT Service Markets: A Systematic Literature Review (Supplementary Material) - Jazayeri, Bahar; Platenius, Marie Christin; Engels, Gregor; Kundisch, Dennis

Das Vielfaltstableau und seine Einsatzmöglichkeiten. Vortrag und Workshop im Rahmen der Fortbildung "Einblicke in andere Förderschwerpunkte" für Seminarausbilder/-innen der berufsbegleitenden Ausbildung zum Erwerb des Lehramts sonderpädagogische Förderung (VOBASOF) an der Qualitäts- und Unterstützungs-Agentur - Landesinstitut für Schule in Soest - Büker, Petra
Zusammen mit der Autorengruppe Vielfaltstableau Januar 2016

Atomic and electronic structures evolution of the narrow band gap semiconductor Ag2Se under high pressure - Naumov, P; Barkalov, O; Mirhosseini, Hossein; Felser, C; A Medvedev, S (Journal of Physics: Condensed Matter)
Non-trivial electronic properties of silver telluride and other chalcogenides, such as the presence of a topological insulator state, electronic topological transitions, metallization, and the possible emergence of superconductivity under pressure have attracted attention in recent years. In this work, we studied the electronic properties of silver selenide (Ag2Se). We performed direct current electrical resistivity measurements, in situ Raman spectroscopy, and synchrotron x-ray diffraction accompanied by ab initio calculations to explore pressure-induced changes to the atomic and electronic structure of Ag2Se. The temperature dependence of the electrical resistivity was measured up to 30 GPa in the 4–300 K temperature interval. Resistivity data showed an unusual increase in the thermal energy gap of phase I, which is a semiconductor under ambient conditions. Recently, a similar effect was reported for the 3D topological insulator Bi2Se3. Raman spectroscopy studies revealed lattice instability in phase I indicated by the softening of observed vibrational modes with pressure. Our hybrid functional band structure calculations predicted that phase I of Ag2Se would be a narrow band gap semiconductor, in accordance with experimental results. At a pressure of ~7.5 GPa, Ag2Se underwent a structural transition to phase II with an orthorhombic Pnma structure. The temperature dependence of the resistivity of Ag2Se phase II demonstrated its metallic character. Ag2Se phase III, which is stable above 16.5 GPa, is also metallic according to the resistivity data. No indication of the superconducting transition is found above 4 K in the studied pressure range.

Features of IT Service Markets: A Systematic Literature Review - Jazayeri, Bahar; Platenius, Marie; Engels, Gregor; Kundisch, Dennis (Proceedings of the 14th International Conference on Service Oriented Computing (ICSOC))
The provision of IT solutions over electronic marketplaces became prominent in recent years. We call such marketplaces IT service markets. IT service markets have some core architectural building blocks that impact the quality attributes of these markets. However, these building blocks and their impacts are not well-known. Thus, design choices for IT service markets have been made ad-hoc until now. Furthermore, only single aspects of such markets have been investigated until now, but a comprehensive view is missing.In this paper, we identify common features and their interrelations on the basis of a systematic literature review of 60 publications using grounded theory.This knowledge provides an empirical evidence on the interdisciplinary design choices of IT service markets and it serves as a basis to support market providers and developers to integrate market features. Thereby, we make a first step towards the creation of a reference model for IT service markets that provides a holistic integrated view that can be used to create and maintain successful markets in the future.

An Evolutionary Robotics Approach to the Control of Plant Growth and Motion: Modeling Plants and Crossing the Reality Gap - Wahby, Mostafa; Hofstadler, Daniel Nicolas; Heinrich, Mary Katherine; Zahadat, Payam; Hamann, Heiko (Proc. of the 10th International Conference on Self-Adaptive and Self-Organizing Systems)
The self-organizing bio-hybrid collaboration ofrobots and natural plants allows for a variety of interestingapplications. As an example we investigate how robots can beused to control the growth and motion of a natural plant, using LEDs to provide stimuli. We follow an evolutionaryrobotics approach where task performance is determined bymonitoring the plant's reaction. First, we do initial plantexperiments with simple, predetermined controllers. Then weuse image sampling data as a model of the dynamics ofthe plant tip xy position. Second, we use this approach toevolve robot controllers in simulation. The task is to makethe plant approach three predetermined, distinct points in anxy-plane. Finally, we test the evolved controllers in real plantexperiments and find that we cross the reality gap successfully. We shortly describe how we have extended from plant tipto many points on the plant, for a model of the plant stemdynamics. Future work will extend to two-axes image samplingfor a 3-d approach.

Self-Organized Construction with Continuous Building Material: Higher Flexibility Based on Braided Structures - Heinrich, Mary Katherine; Wahby, Mostafa; Divband Soorati, Mohammad; Hofstadler, Daniel Nicolas; Zahadat, Payam; Ayres, Phil; Stoy, Kasper; Hamann, Heiko (Proc. of the 1st International Workshop on Self-Organising Construction (SOCO))

Hybrid Societies: Challenges and Perspectives in the Design of Collective Behavior in Self-organizing Systems - Hamann, Heiko; Khaluf, Yara; Botev, Jean; Divband Soorati, Mohammad; Ferrante, Eliseo; Kosak, Oliver; Montanier, Jean-Marc; Mostaghim, Sanaz; Redpath, Richard; Timmis, Jon; Veenstra, Frank; Wahby, Mostafa; et al. (Frontiers in Robotics and AI)

Robot Self-Assembly as Adaptive Growth Process: Collective Selection of Seed Position and Self-Organizing Tree-Structures - Hamann, Heiko; Divband Soorati, Mohammad (IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS 2016))

Collective Decision with 100 Kilobots: Speed vs Accuracy in Binary Discrimination Problems - Dorigo, Marco; Hamann, Heiko; Valentini, Gabriele; Ferrante, Eliseo (Journal of Autonomous Agents and Multi-Agent Systems)

Existence and Properties of Pure Nash Equilibria in Budget Games - Drees, Maximilian

Population Coding: A New Design Paradigm for Embodied Distributed Systems - Hamann, Heiko; Valentini, Gabriele; Dorigo, Marco (10th Int. Conf. on Swarm Intelligence, ANTS 2016)

Robot Gardens: An Augmented Reality Prototype for Plant-Robot Biohybrid Systems - von Mammen, Sebastian; Hamann, Heiko; Heider, Michael (ACM Symposium on Virtual Reality Software and Technology (VRST))

Inspiration-Triggered Search: Towards Higher Complexities by Mimicking Creative Processes - Rybář, Milan; Hamann, Heiko (Proceedings of the Genetic and Evolutionary Computation Conference (GECCO 2016))

On the Definition of Self-organizing Systems: Relevance of Positive/Negative Feedback and Fluctuations - Khaluf, Yara; Hamann, Heiko (ANTS 2016)

Collective Perception of Environmental Features in a Robot Swarm - Valentini, Gabriele; Brambilla, Davide; Hamann, Heiko; Dorigo, Marco (10th Int. Conf. on Swarm Intelligence, ANTS 2016)

Evaluation von Graphpartitionierungsalgorithmen im Kontext von Konfigurierbarer Softwarezertifizierung - Bröcher, Henrik

Economics of Corruption and Crime: An Interdisciplinary Approach to Behavioral Ethics - Dimant, Eugen

JoiningTWIP – TWIP-Steels for Multi-Material Design in Automotive Industry Using Low heat Joining Technologies - Böddeker, Tobias; Ivanjko, Martin; Chergui, Azeddine; Gili, Flavia; Behrens, Sabine; Folgar, Hugo; Runkel, Dirk (6. Fügetechnisches Gemeinschaftskolloquium)

The Impact of Dietary Factors on Glycemic Control, Insulin Sensitivity and Secretion in the First Years after Diagnosis of Diabetes. - Weber, KS; Buyken, Anette; Nowotny, B; Strassburger, K; Simon, MC; Pacini, G; Szendroedi, J; Müssig, K; Roden, M; Group, GDS (Exp Clin Endocrinol Diabetes)

Associations between explorative dietary patterns and serum lipid levels and their interactions with ApoA5 and ApoE haplotype in patients with recently diagnosed type 2 diabetes. - Weber, KS; Knebel, B; Strassburger, K; Kotzka, J; Stehle, P; Szendroedi, J; Müssig, K; Buyken, Anette; Roden, M; Group, GDS (Cardiovasc Diabetol)

Kollektivität und Lehrerkooperation an Grundschulen - Grenzen und Möglichkeiten unterschiedlicher Konzeptionen - Bloh, Thiemo; Bloh, Bea

Lehrerkooperation als Community of Practice – Zur Bedeutung kollektiv-impliziter Wissensbestände für eine kooperationsbedingte Kompetenzentwicklung - Bloh, Thiemo; Bloh, Bea (Journal of Educational Research Online)

Explaining inter-provincial migration in China - Gries, Thomas; Kraft, Manfred; Simon, Manuel (Papers in Regional Science)

Towards an Economic Theory of Destabilization War - Gries, Thomas; Haake, Claus-Jochen (Peace Economics and Peace Science)

The Entrepreneurship Beveridge Curve - Gries, Thomas; Jungblut, Stefan; Naudé, Wim (International Journal of Economic Theory)

Szenariobasierte Synthese verteilter mechatronischer Systeme - Brenner, Christian

Vorausschau und Technologieplanung. 12. Symposium für Vorausschau und Technologieplanung, Heinz Nixdorf Institut, 8. und 9. Dezember 2016 - Gausemeier, Jürgen

Systematik zur Antizipation von Stakeholder-Reaktionen - Peter, Stefan

Rahmenwerk zur Integration des modellbasierten Systems Engineering in die Produktentstehung mechatronischer Systeme - Tschirner, Christian

Flachheitsbasierte Positionsregelungen für Parallelkinematiken am Beispiel eines hochdynamischen hydraulischen Hexapoden - Knoop, Sarah

Listening to learners’ voices: Qualitative aspects of pronunciation learning during study abroad - Müller, Mareike (Journal of Second Language Pronunciation)
This article investigates learners’ perceptions on pronunciation learning in study-abroad contexts from a qualitative perspective. While previous research focused mainly on quantitative measurements of pronunciation gains with mixed results, this study takes a more learner-centered approach and examines the impact of socio-psychological factors on learning foreign pronunciation, which appears to be a highly individual and at times conflict-prone process with which sojourners are confronted. The study draws on the cases of five Canadian students who studied abroad at German universities for one or two semesters. The data collection involved a learning history questionnaire; semi-structured interviews pre-, mid-, and post-sojourn; and bi-weekly e-journals. The data was analyzed and interpreted within the framework of narrative analysis. The results show how sojourners’ beliefs about the importance of pronunciation, community participation, identity-related challenges, and obstacles to pronunciation learning influence and help explain individually different learning behaviors and results.
Keywords: pronunciation learning; study abroad; qualitative approach; narrative analysis; learner beliefs; socio-psychological learning factors

Conceptualizations, images, and evaluations of culture in study abroad students - Müller, Mareike; Schmenk, Barbara (Canadian Journal of Applied Linguistics)
This article focuses on the cultural dimension of sojourners’ learning during study abroad periods. By examining the cases of two Canadian learners of German who studied abroad in Germany for 1 year, we aim to amend discussions in existing research on what kind of cultural learning may take place during study abroad and how cultural learning may be conceptualized and operationalized. Our results suggest that assuming that study abroad leads to a heightened intercultural sensitivity, to more cultural knowledge, and to an increased intercultural competence, is problematic with respect to the conceptual underpinnings of “cultural learning.” The notions of culture that underlie much of what participants consider “cultural learning and experience” often remain essentialist. We therefore propose to replace the interculturality paradigm by a transculturality paradigm as it allows us to capture the complexities of study abroad and cultural learning more accurately.

Gelingensbedingungen für den Aufbau einer forschenden Grundhaltung – eine qualitative vergleichende Fallstudie - Homt, Martina; van Ophuysen, Stefanie

Forschend Lernen in Praxissemester und Lehrerberuf – die Einstellung von Lehramtsstudierenden - Homt, Martina; van Ophuysen, Stefanie

Gelingensbedingungen für die Implementation Forschenden Lernens – eine qualitative vergleichende Fallstudie - Homt, Martina; van Ophuysen, Stefanie

Wie lernt man „forschendes Lernen“? Die Konzeption der Methodenausbildung für Lehramtsstudierende an der WWU Münster und erste Evaluationsergebnisse - Behrmann, Lars; Homt, Martina; Schmidt, Jennifer; van Ophuysen, Stefanie

Zwei Testformate: vergleichbare Ergebnisse? Mathematikabiturklausuren und standardisierte Testaufgaben - Weischenberg, Julia; Eickelmann, Birgit (Zeitschrift für Schulentwicklung und Schulmanagement Baden-Württemberg)

Informationskompetenz als Aufgabe von Schule - Eickelmann, Birgit (Handbuch Informationskompetenz)

Mobiles Lernen und computer- und informationsbezogene Kompetenzen von Achtklässlerinnen und Achtklässlern - Schaumburg, Heike; Prasse, Doreen; Eickelmann, Birgit; Gerick, Julia (ICILS 2013 - Vertiefende Analysen zu computer- und informationsbezogenen Kompetenzen von Jugendlichen)

Perspektiven von Schulleitungen auf neue Technologien in Schule und Unterricht - Gerick, Julia; Eickelmann, Birgit; Drossel, Kerstin; Lorenz, Ramona (ICILS 2013 - Vertiefende Analysen zu computer- und informationsbezogenen Kompetenzen von Jugendlichen)

Der Erwerb von computer- und informationsbezogenen Kompetenzen von Ganztags- und Halbtagsschülerinnen und -schülern im Vergleich - Eickelmann, Birgit; Rollett, Wolfram; Weischenberg, Julia; Vennemann, Mario (ICILS 2013 - Vertiefende Analysen zu computer- und informationsbezogenen Kompetenzen von Jugendlichen)

ICILS 2013 - Vertiefende Analysen zu computer- und informationsbezogenen Kompetenzen von Jugendlichen

Eine Bilanz zur Integration digitaler Medien an Grundschulen in Deutschland aus international vergleichender Perspektive - Eickelmann, Birgit (Neue Medien in der Grundschule 2.0. Grundlagen - Konzepte - Perspektiven)

High-stakes testing and Educational Governance – Insights and innovations in European school systems. Special Issue Editorial - Lorenz, Ramona; Eickelmann, Birgit; Bos, Wilfried (Journal for Educational Research Online (JERO))

Schulische Innovationen im Kontext digitaler Bildung – eine Betrachtung aus der Lehrerperspektive - Gerick, Julia; Eickelmann, Birgit (Zeitschrift Schul-Management)

Digital natives or just kids with smartphones? - The story of ICILS in Germany - Eickelmann, Birgit (IEA Newsletter)

Zur Relevanz informatischer Bildung in der Schule für den Erwerb computer- und informationsbezogener Kompetenzen als Teil von Medienbildung – Ergebnisse für Deutschland und die Schweiz im internationalen Vergleich - Eickelmann, Birgit; Drossel, Kerstin (Zeitschrift MedienPädagogik)

Schule digital – der Länderindikator 2016. Kompetenzen von Lehrpersonen der Sekundarstufe I im Umgang mit digitalen Medien im Bundesländervergleich

Kooperation von Lehrkräften der Sekundarstufe I zum Einsatz digitaler Medien in Lehr- und Lernprozessen in Deutschland und im Bundesländervergleich - Welling, Stefan; Lorenz, Ramona; Eickelmann, Birgit (Schule digital – der Länderindikator 2016. Kompetenzen von Lehrpersonen der Sekundarstufe I im Umgang mit digitalen Medien im Bundesländervergleich)

Die eingeschätzte Relevanz der Phasen der Lehrerausbildung hinsichtlich der Vermittlung didaktischer und methodischer Kompetenzen von Lehrpersonen für den schulischen Einsatz digitaler Medien in Deutschland und im Bundesländervergleich - Eickelmann, Birgit; Lorenz, Ramona; Endberg, Manuela (Schule digital – der Länderindikator 2016. Kompetenzen von Lehrpersonen der Sekundarstufe I im Umgang mit digitalen Medien im Bundesländervergleich)

Additive Fertigungsverfahren im Kontext von Industrie 4.0 - Klemp, Eric; Pottebaum, Jens (Handbuch Industrie 4.0 Bd.3)

Fatigue crack growth behavior and mechanical properties of additively processed EN AW-7075 aluminium alloy - Reschetnik, Wadim; Brüggemann, Jan-Peter; Aydinöz, Mehmet Esat; Grydin, Olexandr; Hoyer, Kay-Peter; Kullmer, Gunter; Richard, Hans Albert (Procedia Structural Integrity)

Stochastic recursive inclusion in two timescales with an application to the lagrangian dual problem - Ramaswamy, Arunselvan; Bhatnagar, Shalabh (Stochastics)

Dokumentenorientierte NoSQL-Datenbanken in skalierbaren Webanwendungen - Eine Analyse am Beispiel von MongoDB und der Webanwendung PINGO - Bach, Christoph; Kundisch, Dennis; Neumann, Jürgen; Schlangenotto, Darius; Whittaker, Michael (HMD Praxis der Wirtschaftsinformatik)

Grundsatzfragen der Abwärmenutzung. Effizienzsteigerungspotenziale in der Industrie durch Abwärmenutzung erschließen. - Philipp, Matthias; Schumm, Gregor; Schlosser, Florian; Hechelmann, Ron-Hendrik; Holzhammer, Uwe (BWK Energie-Fachmagazin)

Hybrid-heating-systems for optimized integration of low-temperature-heat and renewable energy - Schumm, Gregor; Philipp, Matthias; Schlosser, Florian; Hesselbach, Jens; Walmsley, Timothy G.; Atkins, Martin J. (Chemical Engineering Transactions)

Hardware in the Loop Evaluation of a Hybrid Heating System for Increased Energy Efficiency and Management - Schumm, Gregor; Philipp, Matthias; Schlosser, Florian; Hesselbach, Jens; Walmsley, Timothy G.; Atkins, Martin J.

Stackelberg Competition among Intermediaries in a Differentiated Duopoly with Product Innovation - Manegold, Jochen
On an intermediate goods market we consider vertical and horizontal product differentiation and analyze the impact of simultaneous competition for resources and the demand of customers on the market outcome. Asymmetries between intermediaries may arise due to distinct product qualities as well as by reasons of different production technologies. The intermediaries compete on the output market by choosing production quantities sequentially and for the supplies of a monopolistic input supplier on the input market. It turns out that there exist differences in product quality and productivities such that an intermediary being the Stackelberg leader has no incentive to procure inputs, whereas in the role of the Stackelberg follower will participate in the market. Moreover, we find that given an intermediary is more competitive, his equilibrium output quantity is higher when being the leader than when being the follower. Interestingly, if the intermediary is less competitive and goods are complements, there may exist asymmetries such that an intermediary being in the position of the Stackelberg follower offers higher output quantities in equilibrium than when being in the position of the Stackelberg leader.
Keywords: Input Market; Product Quality; Quantity Competition; Stackelberg Competition; Product Innovation

Modelling of temperatures and heat flow within laser sintered part cakes - Josupeit, Stefan; Ordia, Lavish; Schmid, Hans-Joachim (Additive Manufacturing)
Temperature effects in the polymer laser sintering process are an important aspect regarding the process reproducibility and part quality. Depending on the job layout and position within the part cake, individual temperature histories occur during the process. Temperature history dependent effects are for example part warpage, the crystallization rate and powder ageing effects. This work focuses on temperatures and heat flow within laser sintered part cakes. Therefore, a thermal Finite Element (FE) model of a part cake is developed based on experimental in-process temperature measurements. Thermal boundary conditions and properties of the used bulk polymer powder are analyzed and relevant parameters are identified. The model is validated and optimized considering different job heights and ambient conditions during the cooling phase. It is finally possible to predict position-dependent temperature histories as a function of significant job parameters. The model allows a transfer of the results for varied boundary conditions during cooling. In combination with an implementation of built parts, this model will be an important tool for the development of optimized process controls and cooling strategies.

Guard ring induced distortion of the steady velocity profile in a parallel plate rheometer - Schmid, Hans-Joachim; Pieper, S. (Applied Rheology)
The shape and fracture of the free surface frequently limits the measuring range and impedes the use of optical velocimetric techniques in parallel plate and cone plate setups. To prevent this, various kinds of edge guards are often employed. In the present study, we elucidate how an edge guard distorts the steady velocity profile in a parallel plate setup. To this end, we analyzed the velocity field of a strongly shear-thinning fluid, a Newtonian fluid and a set of suspensions via particle image velocimetry in a parallel plate device. Several guard ring sizes were studied. The distortion is described by a simple three parameter model. These parameters are mostly constant for different fluids and suspensions with particle volume fractions below 45%. With increasing radius, the guard ring.s influence approaches a limiting value that we attribute to the influence of the fluid surrounding the gap. Our results indicate a limiting ratio of the difference between plate radius and guard to gap size that should always be exceeded. In the presence of a guard ring, even Newtonian fluids do not exhibit a constant shear rate for most radial distances within the gap. This distortion of the velocity field challenges the simple superposition approach of unguarded device and guard influence that is prevalent in the literature.

Layer-formation of non-colloidal suspensions in a parallel plate rheometer under steady shear - Pieper, Sven; Schmid, Hans-Joachim (Journal of Non-Newtonian Fluid Mechanics)
Suspensions are subject to confinement induced structuring, i.e. layering, at the confining surfaces. While most of the previous work focused on layering in Couette cells, the present study aimed to characterize the resulting layers at the plates of a parallel plate rheometer with regard to their relative particle concentration. The particle concentration profile over the radial distance was characterized for various mean concentrations and gap heights. To this end, we mapped the distribution of fluorescently dyed tracer particles in density and refractive index matched suspensions. The results indicate that layering at the surfaces stabilizes as the ratio between gap height and particle diameter increases. For lower gap heights, i.e. as the suspension approaches a two dimensional state, the layer concentration was non-uniform over the plates. In general, results were quantitatively different for the upper and lower plate and the concentration profiles were noticeably asymmetric. We conclude that this is probably the result of the rheometer loading or the start-up process. The stable layers as well as the inhomogeneous particle distribution in general offer an explanation for the lack of transferability of viscosimetric results between different setups.

Auswahl internationaler Standorte - Wie lassen sich Standortentscheidungen methodisch unterstützen? - Betz, Stefan (ForschungsForum Paderborn)